German Language Maintenance Among German Language Education Alumni of Yogyakarta State University: A Sociolinguistic Study - Lalu Ahmad Rofi; Sulistyowati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Language maintenance is a sociolinguistic phenomenon closely related to the sustainability of speakers' linguistic competence in various social domains. This study identifies internal and external factors that influence the success or failure of German language maintenance among alumni of the German Language Education Program at Yogyakarta State University. A quantitative descriptive approach was used with a questionnaire instrument for 43 respondents. The results show that the dominant internal factors include low motivation (16.7%), laziness to practice (19.0%), and limited personal time (19.0%). The main external factors are an environment that does not support language use (33.3%), the absence of a communication partner (19.0%), and work pressure (11.9%). These findings confirm that language maintenance is strongly influenced by individual motivation and the existence of a stable domain of language use. In the Indonesian context, the German language holds strategic value due to its relevance in international education, technological cooperation, and global mobility. Within this sociolinguistic landscape, alumni of German Language Education programs constitute an important speech community because they represent a group with sustained linguistic competence, institutional training, and ongoing engagement with the language after formal schooling.